The Study of Retinoic Acid Effects on Testicular Development of NMRI Mice - Mehri Azadbakht; Mina Ramezani; Soheila Ebrahimi; Hanieh Moradi (Fasa University of Medical Sciences, 2016)
Background & Objectives: Retinoids are important molecules that regulate crucial processes of development in all vertebrates. In this article, we study the effect of retinoic acid on testis development. Materials & Methods: A group of newborn NMRI mice was chosen to receive intraperitoneally injections of 25 mg/Kg.b.w of retinoic acid and the control group had no injection. After 21 days, the male animals were isolated and sacrificed in 60 days postpartum, and testes were removed from their bodies. Apparent characteristics of the testes of seven mice from each group were observed. In the light microscopic study, these epithelial cells of the tubules were counted and the diameter of seminiferous tubules were measured with statistical T-test analysis and were compared with control group. Results: The findings showed that the weight of the testes in animals that were affected by retinoic acid did not change significantly compared to control group. In germ epithelium of testis, the thickness of the epithelium and the number of the spermatogonia, round and elongated spermatids has decreased significantly compared to the control group (P<0.05). Conclusion: According to the findings of this article, using the retinoic acid after birth has influence on testis development and its seminiferous tubules epithelium. Retinoic acid has an adverse effect on the cell divisions in seminiferous epithelium, therefore the number of affected germ cells decrease. Therefore, the use of vitamin A and its synthetic derivatives like retinoic acid for pregnant women should be done with caution.